Different approach, similar outcomes: the impact of surgical access routes in minimally invasive cardiac surgery on enhanced recovery after surgery - Berger Veith, Sarah; Holst, Theresa; Erfani, Sahab; Pochert, Julia; Dumps, Christian; Girdauskas, Evaldas; Stock, Sina (Frontiers in Cardiovascular Medicine, 2024)
Objectives Enhanced recovery after surgery (ERAS) is a growing phenomenon in all surgical disciplines and aims to achieve a faster functional recovery after major operations. Minimally invasive cardiac surgery (MICS) therefore integrates well into core ERAS values. Surgical access routes in MICS include right anterolateral mini-thoracotomy (MT) as well as partial upper mini-sternotomy (PS). We seek to compare outcomes in these two cohorts, both of which were enrolled in an ERAS scheme. Methods 358 consecutive patients underwent MICS and perioperative ERAS at our institution between 01/2021 and 03/2023. Patients age >80 years, with BMI > 35 kg/m², LVEF ≤ 35%, endocarditis or stroke with residuum were excluded. Retrospective cohort analysis and statistical testing was performed on the remaining 291 patients. The primary endpoint was successful ERAS, secondary endpoints were the occurrence of major bleeding, ERAS-associated complications (reintubation, return to ICU) as well as access-related complications (wound infection, pleural and pericardial effusions). Results 170 (59%) patients received MT for mitral and/or tricuspid valve surgery (n = 162), closure of atrial septal defect (n = 4) or resection of left atrial tumor (n = 4). The remaining 121 (41%) patients had PS for aortic valve repair/replacement (n = 83) or aortic root/ascending surgery (n = 22) or both (n = 16). MT patients’ median age was 63 years (IQR 56–71) and 65% were male, PS patients’ median age was 63 years (IQR 51–69) and 74% were male. 251 (MT 88%, PS 83%, p = 0.73) patients passed through the ERAS program successfully. There were three instances of reintubation (2 MT, 1 PS), and three instances of readmission to ICU (2 MT, 1 PS). Bleeding requiring reexploration occurred six times (3 MT, 3 PS). There was one death (PS), one stroke (MT), and one myocardial infarction requiring revascularization (MT). There were no significant differences in any of the post-operative outcomes recorded, except for the incidence of pericardial effusions (MT 0%, PS 3%, p = 0.03). Conclusions Despite different surgical access routes and underlying pathologies, results in both the MT and the PS cohort were generally comparable for the recorded outcomes. ERAS remains safe and feasible in these patient groups.